(untitled) (Perner’s Contacts, 2011)
The article analyzed the actualy missing tools in the technological process of road oversize transport, especially in the preparatory phase. To individual absebces are got in solutions.The Author has also dealt with a problem involving thespecial transportation during crisis situation.